Promoting Competition in Local Markets in Mexico : A Subnational Application of the World Bank Group's Markets and Competition Policy Assessment Tool - World Bank (World Bank, Washington, DC, 2018)
Stagnant productivity growth and high disparities in productivity levels across Mexican states have been holding back economic growth. In general, Mexico’s federal government has a solid competition policy framework in place. Subnational regulations in transport, agriculture, tourism, retail, and other sectors are holding back the potential of local economies to grow and provide consumers with affordable goods. Anticompetitive regulations for professionals such as notaries also increase the cost of doing business. The World Bank Group (WBG) was requested to address a critical gap and to pilot a reform-oriented engagement on competition policy at the subnational level. WBG engaged to motivate an actionable reform plan that can unlock competition in key markets at the local level. This note discusses the main findings of the WBG’s markets and competition policy assessment tool (MCPAT) application to various subnational governments in Mexico and the initial reform experience. It draws on the results of multiple pieces of analysis and implementation support projects since 2012 to assess, identify, prioritize, and modify regulations that restrict competition at the subnational level in key markets. This note is structured as follows: section 1 gives an introduction, section 2 discusses the international experience on the role of competition at the local level for development. Section 3 provides a brief presentation of the methodological steps of the MCPAT subnational application. Section 4 discusses incidences of anti-competitive regulation (some of which have been removed) to exemplify their harmful effect. Section 5 provides several examples of how to prioritize and design reforms based on how government interventions at the subnational level interact with particular features of subnational Mexican markets, as well as based on their feasibility and their potential effects.